Financial crisis resolution and federal reserve governance: Economic thought and political realities - Bernard Shull (Levy Economics Institute of Bard College, 2014)
The Federal Reserve has been criticized for not forestalling the financial crisis of 2007-09, and for its unconventional monetary policies that have followed. Its critics have raised questions as to whom, if anyone, reins in the Federal Reserve if and when its policies are misguided or abusive. This paper traces the principal changes in governance of the Federal Reserve over its history. These changes have, for the most part, developed in the wake of economic upheavals, when Fed policy has been challenged. The aim is to identify relevant issues regarding governance and to establish a basis for change, if needed. It describes the governance mechanism established by the Federal Reserve Act in 1913, traces the passing of this mechanism in the 1920s and 1930s, and assays congressional efforts to expand oversight in the 1970s. It also considers the changes in Fed policies induced by the financial crisis of 2007-09 and the impact of the Dodd-Frank Wall Street Reform and Consumer Protection Act of 2010. It concludes that the original internal governance mechanism, a system of checks and balances that aimed to protect all the important interest groups in the country, faded in the 1920s and was never adequately replaced. In light of the Federal Reserve's continued growth in power and influence, this deficiency constitutes a threat not only to "stakeholders" but also to the independence of the Federal Reserve itself.
Keywords: E58; N2; 330; Central Banks; Federal Reserve; Governance